Photo-microdomains in ferroelectrics: formation and light scattering caused by them - Morozovska, A.N.; Eliseev, E.A.; Obukhovsky, V.V.; Lemeshko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
We propose the theory of the micro-domains (MD) formation in ferroelectric photorefractive crystals appeared under steady illumination by laser beam perpendicular to the polar axis. The crystal has the donor level made of photoactive impurity atoms. The longitudinal photovoltaic current leads to surface charges accumulation at the light spot boundary. These charges are localized at the nano-clusters of different size and charge density randomly distributed in the thin transition layer between light and dark. Each such cluster can be treated as the seeding for one MD growth. Therefore the numerous MD appear around the illuminated area. The micro-domain shape and physical properties are studied in the phenomenological Ginsburg-Landau-Devonshire theory framework with respect to the screening effects of ferroelectric medium. We obtained, that when the cluster charge density is more that the critical one, MD become very long and thin ones and in principle can intergrow through the perfect sample. In such a case they could be easily registered experimentally. So, exactly due to the transverse modulation effects the MD length can be sharply increased from the dozens of microns and up to the crystal length. All theoretical results are in a good qualitative agreement with our experiments on photo- micro-domain formation in LiNbO₃ crystals and light scattering caused by them.